2010
DOI: 10.3892/ijo_00000726
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vandetanib on adenoma formation in a dextran sodium sulphate enhanced ApcMIN/+ mouse model

Abstract: The Apc(MIN/+) mouse is a well-characterised model of intestinal tumourigenesis in which animals develop macroscopically detectable adenomas. However, most of the adenomas are formed in the small intestine and resolution of events in the colon, the most relevant site for human disease, is limited. Inducing colitis with dextran sodium sulphate (DSS) can selectively enhance the development of lesions in the colon. We demonstrated that a DSS pre-treatment is well tolerated and effective at inducing colon adenomas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…[3][4][5][6] The information available regarding the molecular and genetic pathways that result in colorectal cancer, such as tumor suppressor genes, DNA mismatch repair (MMR) genes and proto-oncogenes, has increased markedly. The specific contributing mutations in genes such as adenomatous polyposis coli (APC) [7][8][9][10][11] and MMR 8, [12][13][14][15][16][17][18] have been investigated intensively. Mutations or deficiencies in APC and MMR contribute significantly to the development of age-related or familial colonic neoplasia and sporadic or mucosal damage-related neoplasia, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] The information available regarding the molecular and genetic pathways that result in colorectal cancer, such as tumor suppressor genes, DNA mismatch repair (MMR) genes and proto-oncogenes, has increased markedly. The specific contributing mutations in genes such as adenomatous polyposis coli (APC) [7][8][9][10][11] and MMR 8, [12][13][14][15][16][17][18] have been investigated intensively. Mutations or deficiencies in APC and MMR contribute significantly to the development of age-related or familial colonic neoplasia and sporadic or mucosal damage-related neoplasia, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…When the whole SB was considered (SB All) barasertib reduced the mean number of adenomas by 39% from 52.31±6.18 to 31.87±5.64 (P<0.05); Table II. There were much fewer adenomas in the colon than in the SB, due to the lower incidence of adenomas occurring in the colon in this model (22). Although a similar reduction in the number of adenomas in the colon (38%) was seen in barasertib versus vehicle-treated mice, this did not reach statistical significance (Table II).…”
Section: Barasertib Treatment Leads To Antitumor and Pharmacodynamic mentioning
confidence: 75%
“…The SB was divided into three equal sections: proximal (SB1), middle (SB2) and distal (SB3). These sections and the colon were dissected longitudinally using a recently described cutting guide (22) and spread onto filter paper before being fixed in Carnoy's fluid for 1 h and stored in 70% ethanol until analysis. Macroscopic adenoma quantification was carried out using a dissecting microscope as described previously (23) to assess the number, size and overall tumor burden.…”
Section: Methodsmentioning
confidence: 99%
“…Mice exposed to 1% DSS did not show a statistically significant difference in tumor burden in the ileum after 2 weeks (Figure S2a), which is consistent with previous studies (Ohtsuka and Sanderson, 2003; Tanaka et al ., 2006). It is noteworthy that in several studies, it was observed that DSS also induced tumorigenesis in the ileum (Cooper et al ., 2001; Tanaka et al ., 2006; Alferez et al ., 2010; Tanaka, 2012), however these studies utilized higher concentrations of DSS and a longer timepoint, producing a stronger effect (Tanaka et al ., 2006; Alferez et al ., 2010). In contrast to the ileum, we observed a dramatic increase in tumors in the colon (Figure 2e), and these were primarily concentrated in the distal region (which is consistent with previous studies of DSS‐induced colonic inflammation) (Kitajima et al ., 2000; Seamons et al ., 2013; Biton et al ., 2018).…”
Section: Resultsmentioning
confidence: 99%